How The Forms of Fatal Linguistic Errors in A Job Application Letter? - Rina Maulindah; Indrya Mulyaningsih; Tati Sri Uswati (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
Job application letters are included in the class of official letters so that there are certain aspects that must be considered in their administration. One of these aspects is the language aspect. This study aims to describe the forms of language, such as: spelling, diction, and sentences used in job application letters at the Special Job Exchange for the Presidential Vocational School of Cirebon City and Indomaret, Kejuden Village, Cirebon Regency. This research is a qualitative research. Techniques and data instruments used in this study were documentation techniques and data cards. In addition, the observation technique with the advanced note-taking technique was used to study the data in this study. The data analysis technique used the miles model and Huberman. Based on the results of the analysis, it can be concluded that there are 223 language errors used in job application letters, with details: 161 spelling errors, 19 diction errors, and 43 errors.